Sirtuin 1 in Chronic Kidney Disease and Therapeutic Potential of Targeting Sirtuin 1 - Yan, Jiayi; Wang, Jue; He, John Cijiang; Zhong, Yifei (Frontiers in Endocrinology, 2022)
The prevalence of chronic kidney disease (CKD) is increasing worldwide and is a major public health burden. CKD eventually progresses to end-stage kidney failure and is associated with high morbidity and mortality. Sirtuin 1 (SIRT1) belongs to an evolutionarily conserved family of NAD+-dependent deacetylases that has significant renal protective effects. SIRT1 exerts renal protective effects through its regulation of fibrosis, apoptosis, and senescence, oxidative stress, inflammation and aging process. SIRT1 also has protective effects against vascular calcification and therefore could be developed as a therapy for CKD complication. In this narrative review, we will give an overview of the recent progress on the role of SIRT1 and its molecular targets as well as SIRT1-modulated biological processes, with a focus on the CKD. We will also discuss potential therapeutic approach by activating SIRT1-related pathway in patients with CKD. The purpose is to hope to provide some insights on the future direction of the research in the field of SIRT1 for CKD.